Diagnosis of gall bladder agenesis is a pitfall - Taha, Sami Mahjoub; Ibnuof, Mohammed Ahmed; Masaad, AbdAlMagid; Mohammed, Mohamed EL-Imam; Mohammed, Kamal; Mustafa, Gamal; Yaseen, Diaa Eldinn (Gezira Journal of Health Sciences; Vol 8 No 2 (2012), 2012)
_